Ethnobotanical study of medicinal plants used by Bisaya communities along Padas river, Beaufort, Sabah / Irmah Anwar - Anwar, Irmah (2016)
This paper presents the results of ethnobotanical studies on medicinal plants used traditionally by the Bisaya Communities along Padas River, Beaufort, Sabah. A total of 63 species of medicinal plants were noted and collected during the surveys. To this extent, several species of medicinal plants such as Phyllantusniruri, Orthosiphon aristatus, Andropogon nardus, Cacalia cylindriflora, Melastoma malabathricum were identified to be naturally distributed on that area. Most plant parts (boiled and drink) identified such as (bark, root, seeds, fruit, and leaf) serve as major source of active ingredient to be used by the traditional practitioners. Several visits were made to the villages along the Padas River between August 2015 and November 2015 for collection, identification and naming of the plants used. Data was collected through the use of questionnaires and personal interviews during the field trips.